New therapeutic targets for osteoarthritis pain - Walsh, David A.; Stocks, Joanne (Sage, 2017)
Osteoarthritis (OA), the most common form of arthritis, causes pain and disability, as well as emotional distress. While total joint replacement is one of the most effective treatments available for improving the quality of life in people with severe OA, it is not suitable for all patients and all joints. Current pharmacological analgesics have limited efficacy, and their use is often restricted by adverse events. Medications that might reduce pain by slowing or preventing structural disease remain elusive. Our increasing understanding of the complex mechanisms that underlie OA pain offers a wide range of potential new treatment targets. New drugs for OA pain might come from repurposing those developed for other conditions, as well as novel compounds targeting pain mechanisms specific to the joint. Here we discuss the mechanisms of OA pain and its therapeutic implications. We explore evolving treatment modalities, including combination treatment. We review recent research and patents pointing to future OA therapies. We discuss the potential for biomarkers to facilitate drug development and targeting.